O‘SMIRLARDA TASHABBUSKORLIK FAZILATLARINI SHAKLLANTIRISHNI O‘RGANISHGA YONDASHUVLAR TAHLILI - Mambetyarov, Sh. (SCIENCE and SOCIETY, 2024)
This article provides information about the need for citizens who can take initiative and take a new look at the current problems of modern society, and about some approaches to learning the formation of important human qualities such as mobility, competitiveness and initiative qualities in teenagers.
Keywords: initiative; experimental; intellectual; Leadership; guidance; adolescent; integration; emotional leader; individual